How does digital financial inclusion improve Chinese county-level carbon productivity? - Lei, Zhaoyuan; Zhang, Chunxia; Li, Rong; Cai, Linmei; Zhou, Yan (Frontiers in Climate, 2025)
China has put forward the “carbon peak and carbon neutral” climate commitment, but as the basic unit of the national economy, China’s county economy is facing the double pressure of economic growth and emission reduction. Based on panel data spanning 1677 Chinese counties from 2014 to 2022, this study employs fixed-effects, mediation, moderation, and quantile models to analyze and derive the following conclusions. (1) digital financial inclusion has a significant impact on the improvement of county carbon productivity, with an influence coefficient as high as 19.44%. (2) Digital financial inclusion enhances county-level carbon productivity by promoting technological innovation and industrial structure upgrading. The positive moderating effects of traditional finance and urbanization further amplify this impact. Digital financial inclusion exerts a strong positive effect on carbon productivity at lower quantiles, but its influence diminishes at median quantiles and turns negative at higher quantiles. This pattern reflects diminishing marginal returns and tightening resource constraints as development approaches the technological frontier. (3) Only digitalization level and coverage breadth of digital financial inclusion have a significant positive impact on county carbon productivity, and the effect of digitalization level is almost twice that of coverage breadth. The influence coefficients of digital inclusive finance on carbon productivity in the Yangtze River Economic Belt and the Yellow River Basin are 21.72% and 27.82%, respectively, which are more significant than those in other places. This paper recommends prioritizing low-carbon industrial development, shifting focus to less-developed regions to leverage latecomer advantages, and embedding carbon productivity targets into regional strategies with incentive mechanisms to drive sustainable growth.